Peran Dan Tantangan Guru Pendidikan Agama Hindu Dalam Menerapkan Sikap Pluralisme Siswa - Surya, Ida Ayu Melanie (Jayapangus Press, 2022)
Indonesia is a dominant country with a diverse population which has the potential to cause horizontal conflict. So, a country will be great if its people have awareness, as well as an attitude of tolerance and mutual respect in the world of education. The experience of pluralism in schools can minimize various problems that arise both at the national and global levels. The task of a Hindu religious education teacher is that of a functionary who has great duties and responsibilities and serves as the spearhead of educating students. The aim of this research is to determine the role and challenges of Hindu religious education teachers in implementing students' attitudes of pluralism. The use of descriptive qualitative research methods with data collection using observation techniques and documentation studies. The results of carrying out this research are as follows: 1) Teacher as facilitator, in the teacher's role as facilitator the teacher helps students by dedicating teaching materials and providing learning facilities. 2) Teacher as Motivator, the role of the teacher as a motivator is to increase students' interest in learning, creating an interesting learning environment. So, students will have higher motivation to participate in the learning process. 3) The teacher as a guide, with the presence of a teacher is expected to be able to cover the morals conveyed to students, in the form of tools, individuals and materials used. 4) Teachers as educators, the teacher's job is not only to provide information to students to understand the lesson, but also to guide and train students is a teacher's job besides educating. Apart from these roles, there are also several challenges faced by teachers, such as the challenge of facing the influence of globalization and facing ethnocentrism.